The Role of Civic Education Teachers as Evaluators in Improving Learning Discipline of Class VII Students of SMP Muhammadiyah 24 Aek Kanopan - Dalimunthe, Hamidah; Amin, Zulkifli (Lembaga Riset Mutiara Akbar, 2024)
This research aims to explain the role of Pancasila and Citizenship Education (PPKn) teachers as evaluators in improving student learning discipline at SMP Muhammadiyah 24 Aek Kanopan. This research uses a qualitative approach with descriptive methods. The subjects in this research were Pancasila and Citizenship Education (PPKn) teachers and students. Data collection techniques use observation, interviews and documentation. The analysis technique is carried out in three stages of activities, namely data reduction, data presentation and conclusions. The results of this research in improving student learning discipline, Pancasila and Citizenship Education (PPKn) teachers as evaluators carry out continuous learning evaluations to see student success in learning and can improve student learning discipline if the results of student learning evaluations have not shown success. Civics teachers as evaluators, they compare students' abilities in answering questions and playing a role in group collaboration. Apart from that, Civics teachers also play a role in developing skills in guiding small group discussions, organizing lessons, and maintaining school rules